Regulating Islam by Regulating Public Housing - Sofie Aaltonen (Religion & Human Rights, 2026)
Abstract This article analyses the construction of the “non-Western” legal subject in the 2018 public housing policy, commonly known as the “Ghetto law,” considering the Advocate General’s opinion in February 2025 and the Court of Justice of the European Union’s subsequent ruling in December 2025. I demonstrate how the Danish Government engages in lawfare to subvert the rule of law and suppress the realisation of Muslims’ legal rights in Denmark. As such, the ghetto law is understood as an expression of the expansion of available legal structures, norms, and processes (juridification) to regulate Islam and to capture the subjectification of Muslims in law. The article also reflects on how international courts mediate between states and civil society on such contentious human rights issues. It suggests that case law can both hinder and promote the transfer of a restrictive view of rights across European jurisdictions.